A combined series active filter and passive filters for harmonics, unbalances and flicker compensation - Pinto, J. G. (2007)
This paper describes a combined operation involving a series active filter and shunt passive filters for three-phase three-wire systems. The series active filter is able to minimize Power Quality problems like unbalances, harmonics and flicker observed at the system voltages. Another task for the series active filter is to damp possible resonances involving the passive filters and the system impedance. The shunt passive filters are designed to drain harmonic current-components generated by the load. The control strategy of the series active conditioner is based on the instantaneous power theory on α-β-0 reference frame, together with a robust synchronizing circuit PLL (Phase-Locked-Loop). A dc-link voltage controller, applied to the series conditioner, is also introduced due to the fact that there is only a single capacitor at the inverter dc-side. Simulation results on PSCAD®/EMTDC™ are presented in order to verify the performance involving a combined operation of passive and active filters.